The relationship between perceived usability and perceived credibility of Middle school teachers in using AI chatbots - Van-Da Can; Van-Hanh Nguyen (Cogent Education)
This study investigated the relationship between perceived usability and perceived credibility of middle school teachers in using artificial intelligence (AI) chatbots. Perceived usability was assessed through four dimensions: perceived usefulness, ease of use, ease of learning, and satisfaction. Perceived credibility was evaluated across three dimensions: source credibility, media credibility, and message credibility. The study employed an online survey method to collect data from 423 middle school teachers and analyzed the data using Pearson correlation. The results revealed a positive correlation between perceived usability and perceived credibility across all dimensions. The correlation coefficients had the lowest value of 0.686 and the highest value of 0.801, showing the strength of associations in the level of strong correlation. When teachers perceive AI chatbots as useful, easy to use, easy to learn, and satisfying, they are more likely to trust these tools and apply them in their professional work. These findings suggest that improving teachers’ usability of AI chatbots can enhance their credibility with these tools. This research offers valuable insights for educational policymakers, technology developers, and school administrators seeking to effectively integrate AI technologies into education.